Hop/Sti1 phosphorylation inhibits its co-chaperone function - Röhl, Alina (EMBO Rep, 2015)
In eukaryotes, the molecular chaperones Hsp90 and Hsp70 are connected via the co-chaperone Sti1/Hop, which allows transfer of clients. Here, we show that the basic functions of yeast Sti1 and human Hop are conserved. These include the simultaneous binding of Hsp90 and Hsp70, the inhibition of the ATPase activity of Hsp90, and the ability to support client activation in vivo. Importantly, we reveal that both Hop and Sti1 are subject to inhibitory phosphorylation, although the sites modified and the influence of regulatory phosphorylation is species specific. Phospho-mimetic variants have a reduced ability to activate clients in vivo and different affinity for Hsp70. Hop is more tightly regulated, as phosphorylation affects also the interaction with Hsp90 and induces structural rearrangements in the core part of the protein.